2006
DOI: 10.1021/om060096r
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and DFT Studies of Cationic Imido Titanium Alkyls:  Agostic Interactions and C−H Bond and Solvent Activation Reactions of Isolobal Analogues of Group 4 Metallocenium Cations

Abstract: Synthesis, reactions, and DFT studies of macrocycle-supported imido titanium alkyl cations derived from Ti(N t Bu)(Me 3 [9]aneN 3 )R 2 (R ) Me (1) or CH 2 SiMe 3 (2)) are described (Me 3 [9]aneN 3 ) 1,4,7trimethyltriazacyclononane). Reaction of 1 with 1 equiv of [Ph 3 C][BAr F 4 ] or BAr F 3 (Ar F ) C 6 F 5 ) in C 6 D 5 Br afforded the methyl cation [Ti(N t Bu)(Me 3 [9]aneN 3 )Me] + (6 + ), whereas with half an equivalent of [Ph 3 C][BAr F 4 ] the fluxional methyl-bridged homo-binuclear cation [Ti 2 (N t Bu) 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
100
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(104 citation statements)
references
References 117 publications
(208 reference statements)
4
100
0
Order By: Relevance
“…Quantitative conversion of 9 to cationic monoalkyl complex 9 + was observed in the 1 H NMR spectrum by the concomitant appearance of signals attributed to the formation of Me 3 SiCH 2 CPh 3 (73.2 % as two isomers in a ca. 2:1 ratio)39 and Ph 3 CH (26.8 %)39 as side products. 1 H NMR (400 MHz, C 6 D 6 /C 6 D 5 Br, 293 K, selected data): δ =0.46 (br s, 2 H, YC H 2 SiMe 3 ), −0.12 (s, Me 3 SiCH 2 CPh 3 of isomer A), −0.04 (s, 9 H, YCH 2 Si Me 3 ), 0.10 (s, Me 3 SiCH 2 CPh 3 of isomer B), 1.20 (m, 12 H, CH(C H 3 ) 2 ), 1.34 (s, 6 H, CH 3 ), 2.03 (s, Me 3 SiC H 2 CPh 3 of isomer B), 2.16 (s, Me 3 SiC H 2 CPh 3 of isomer A), 3.16 (m, 2 H, C H (CH 3 ) 2 ), 5.52 ppm (s, Ph 3 CH).…”
Section: Methodsmentioning
confidence: 98%
“…Quantitative conversion of 9 to cationic monoalkyl complex 9 + was observed in the 1 H NMR spectrum by the concomitant appearance of signals attributed to the formation of Me 3 SiCH 2 CPh 3 (73.2 % as two isomers in a ca. 2:1 ratio)39 and Ph 3 CH (26.8 %)39 as side products. 1 H NMR (400 MHz, C 6 D 6 /C 6 D 5 Br, 293 K, selected data): δ =0.46 (br s, 2 H, YC H 2 SiMe 3 ), −0.12 (s, Me 3 SiCH 2 CPh 3 of isomer A), −0.04 (s, 9 H, YCH 2 Si Me 3 ), 0.10 (s, Me 3 SiCH 2 CPh 3 of isomer B), 1.20 (m, 12 H, CH(C H 3 ) 2 ), 1.34 (s, 6 H, CH 3 ), 2.03 (s, Me 3 SiC H 2 CPh 3 of isomer B), 2.16 (s, Me 3 SiC H 2 CPh 3 of isomer A), 3.16 (m, 2 H, C H (CH 3 ) 2 ), 5.52 ppm (s, Ph 3 CH).…”
Section: Methodsmentioning
confidence: 98%
“…(also in C 6 D 6 ). [49] Since it is known that average 1 J CH values of methyl groups are very sensitive probes of the effective electronegativity of the metal to which they are attached, [50] it can be concluded that the effective charge of the Zn atoms in these directly related zwitterionic complexes is the same and that the metal occupies more or less the same Furthermore, in all instances only k 3 N-coordinated Tpmd ligands have been found. To gain further insight into the structures and reactivity patterns of the new sandwich and half-sandwich compounds and information on experimentally non-observable systems, we carried out a series of DFT calculations (RI-DFT/BP86/def2-TZVP) [53] using the TUR-BOMOLE program (see Supporting Information).…”
Section: N-mentioning
confidence: 99%
“…It has to be noted that it is slightly shorter than the one found in (3) (2.5610(8) Å)9, and significantly shorter than the ones found in complexes of the general formula {(µ,η 5 :η 5 )Pn † } 2 [Ti(EPh)] 2 (E = S, Se, Te) (2.6519 9, 2.6581 15and 2.6530(9) Å respectively),8 d which also derive from the oxidative addition of PhEEPh across the Ti=Ti double bond in (1). Interestingly, the Ti-N bond distance is significantly shorter than a dative N→Ti bond (N = pyridine, 15,16 Me 3 [ane]N 3 16 ), which is typically found in the range between 2.2-2.4 Å, and falls between the bond lengths found for terminal (longer) and bridging (shorter) Ti amide bonds.…”
Section: Resultsmentioning
confidence: 99%